Analysis of Supervision Forms for Communities Carrying Out Destructive Fishing in West Sulawesi Waters - Laitupa, Salma; Sabrina, Dian Fitri; Kartika, Eka Dewi; Syam, Sitti Mutmainnah (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2024)
The behavior of fishermen engaging in harmful practices, such as bombing and use forbidden fishing gear, adversely affect the sustainability of the marine ecosystem. The legal question addressed in this article is to the kind of monitoring exercised by the community engaged in destructive fishing in the waters of West Sulawesi. The oversight of the community engaged in destructive fishing is characterized by inherent supervision from the Provincial and Regency Marine and Fisheries Service, internal oversight by the Regional Office of the Ministry of Marine Affairs and Fisheries, and external supervision by the Water and Air Police (Polairud). However, the supervision of destructive fishing in the waters of West Sulawesi is notably ineffective, with patrols occurring only in response to reports from fellow traditional fishermen to the government